Wingit Cosmology, Nusantara Cultural Wisdom, and Accounting Information Systems as Transformative Instruments of Indonesia's Dark Tourism Industry: A Comprehensive Literature Review - Ignatius Oki Dewa Brata; Sri Astuti Pratminingsih; Hasti Pramesti Kusnara; Rizky Ferari Oktavian; Yus Djunaedi Rusli; Dede Sugandi; Siti Wulandari (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
Dark tourism encompasses visitation to traumatic historical sites, memorial monuments, conflict museums, and disaster locations, representing a rapidly growing segment of Indonesia’s tourism industry. The hospitality sector demands communication approaches integrating Nusantara local wisdom values, including the Javanese cosmological framework of wingit (sacred-haunted) and angker (spiritually inhabited) spaces, into destination management practice. This study synthesises peer-reviewed scientific literature published between 2021 and 2026, organised around three integrated foci: (1) communication strategies grounded in Nusantara cultural values, (2) Javanese wingit cosmology as a form of indigenous heritage management, and (3) Accounting Information Systems (AIS) as an accountability and governance infrastructure. A narrative thematic literature review methodology was applied to a corpus of 95 sources comprising 50 Scopus Q1–Q3 journals, 35 Sinta 1–3 journals, and 12 Scopus journals in the domain of AIS. Key empirical findings indicate that hospitality narratives integrating wingit cosmology increase visitor satisfaction by an average of 31%; the gotong royong (communal cooperation) approach yields satisfaction scores 23% above the mean; and Balanced Scorecard-integrated AIS improves operational efficiency by 21%. The MKHDTBN model proposes a four-layer integrative framework combining cultural value foundations, professional communication competence, narrative management systems, and digital-accounting infrastructure for dark tourism hospitality management in Indonesia.